2011
DOI: 10.4067/s0716-10182011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriemia en daño hepático crónico

Abstract: Los autores manifiestan no tener conflictos de interés.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the contrary, Staphylococcus spp. are the most common Grampositive bacteria found in patients with LC and bacteremia [17,64,65,67,68,70]. Several studies reported no significant differences in either the severity of liver dysfunction or short-term prognosis between patients with bacteremia induced by Gram-positive bacteria and those infected with Gram-negative bacteria [64][65][66].…”
Section: Causative Organisms Detected In Patients With Lc and Bacteremiamentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Staphylococcus spp. are the most common Grampositive bacteria found in patients with LC and bacteremia [17,64,65,67,68,70]. Several studies reported no significant differences in either the severity of liver dysfunction or short-term prognosis between patients with bacteremia induced by Gram-positive bacteria and those infected with Gram-negative bacteria [64][65][66].…”
Section: Causative Organisms Detected In Patients With Lc and Bacteremiamentioning
confidence: 99%
“…Susceptibility to bacteremia [2,15,28,64,67,71,72] and the subsequent short-term prognosis [64,69,70,72,73] in patients with LC are correlated with the severity of LC, which is an independent risk factor for mortality in patients with LC and bacteremia [17]. Moreover, the possibility of the development of renal impairment is significantly higher among patients with bacteremia than among those with negative blood culture [68].…”
Section: Predictors Of Susceptibility and Prognosis In Patients With ...mentioning
confidence: 99%